High Prevalence of Carbapenemase-Producing Acinetobacter baumannii in Wound Infections, Ghana, 2017/2018 - Mathieu Monnheimer; Paul Cooper; Harold K. Amegbletor; Theresia Pellio; Uwe Groß; Yvonne Pfeifer; Marco H. Schulze (Microorganisms, 2021)
Three years after a prospective study on wound infections in a rural hospital in Ghana revealed no emergence of carbapenem-resistant bacteria we initiated a new study to assess the prevalence of multidrug-resistant pathogens. Three hundred and one samples of patients with wound infections were analysed for the presence of resistant bacteria in the period August 2017 till March 2018. Carbapenem-resistant Acinetobacter (A.) baumannii were further characterized by resistance gene sequencing, PCR-based bacterial strain typing, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST “Oxford scheme”). A. baumanni was detected in wound infections of 45 patients (15%); 22 isolates were carbapenem-resistant. Carbapenemases NDM-1 and/or OXA-23 were detected in all isolates; two isolates harboured additionally OXA-420. PFGE and MLST analyses confirmed the presence of one A. baumannii strain in 17 patients that was assigned to the worldwide spread sequence type ST231 and carried NDM-1 and OXA-23. Furthermore, two new A. baumannii STs (ST2145 and ST2146) were detected in two and three patients, respectively. Within three years the prevalence of carbapenem-resistant A. baumannii increased dramatically in the hospital. The early detection of multidrug-resistant bacteria and prevention of their further spread are only possible if continuous surveillance and molecular typing will be implemented.